Analysis of User Attitudes Towards the Attributes of the Simpel Dukcapil Web Application in Bengkalis District - Jushermi, Jushermi; Adnan, Adnan; Pratiwi, Dian (West Science Interdisciplinary Studies, 2025)
This study aims to analyze the fishbein attitude of users of the Simpel Dukcapil Web Application in Bengkalis District. This study uses a type of quantitative research with a population of all Bengkalis Regency residents who have used the Simpel Dukcapil Web Application in processing population documents. The sampling technique uses the proportionate stratified random sampling method with a sample size of 100 respondents. The data analysis technique is processed using the fishbein multiattribute method. The results showed that the total attitude value (Ao) of the Simpel Dukcapil Web Application users generated was 145.6705 which was included in the interval scale range of 98-146, which is in a fairly good category. Researchers chose to use 10 (ten) attributes of the Simpel Dukcapil Web Application in this study, namely accuracy, completeness, relevance, updates, security, reliability, availibility, navigation map, search engine, and browser compatibility. The attribute with the highest value level of importance (ei) is Navigation Map with a value of 4.08. The attribute with the highest value of confidence level (bi) is Accuracy with a value of 4.34. The overall attitude of users towards the Simple Dukcapil Web Application in this study is positive.